EVOLVING INFORMATION TECHNOLOGY: OPPORTUNITIES AND CHALLENGES (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
The rapid Information technology evolution is fast becoming a change agent in the ways we conduct business and social interaction. Due to the increasing number of regulations and policies regarding information technology and also sustainable development, the issues of the cost, efficient, sharing, reuse and recycling matters have become the core challenges. As a consequence, this paper discusses the current physical infrastructure, broadband speed, and increasing bandwidth, that has lead to the transition of the television, radio broadcasting, and print media to digital technology convergence. The convergence of new technology is expected to continue evolving over the next decade, creating new opportunities and challenges. Location based services are expected to evolve through devices or objects with radio frequency identification (RFID) and Global Positioning System (GPS) connectivity. Traditional and new media are and will keep on increasing the social networking market due to the growth in online advertising revenue. Cloud computing will offer scale flexibility and cost efficiency. It will have the potential to be highly disruptive to desktop computing technology within the next few years. The paper highlights some opportunities, challenges and suggests some risks mitigation strategies.Â